Phosphatase activity in the rhizosphere and root of mycorrhizal teak seedlings with three levels of NPK fertilization - CORRYANTI CORRYANTI; J. SOEDARSONO; B. RADJAGUKGUK; S. M. WIDYASTUTI (Biodiversitas Journal of Biological Diversity, 2007)
To examine the phosphatase alkaline activity of VA mycorrhizal fungi in the rizhosphere and in root, teak seedlings inoculated spores of VA mycorrhizal fungi were grown in sterilized soils. Teak seedlings were fertilized with NPK fertilizer consisting three levels, i.e. 0; 0.0625; 0.125 g per seedling. Phosphatase alkaline in rizhosphere was measured in terms of pNP on soil dry weight basis, meanwhile alkaline phosphatase activity in roots were quantified in using method developed by Tisserant. The results showed that alkaline phosphatase activity increased on inoculated seedlings compare to with uninoculated. NPK fertilization of 0.0625 g per seedling and inoculation on teak seedlings showed alkaline phosphatase activity in range 90-201 EU, and in roots indicated in range 14-72%. Gigaspora sp inoculation on teak seedlings was showing the highest of alkaline phosphatase activity. Increasing phosphatase alkaline activity relevant to hyphae growth, and increasing of root infection decreased alkaline phosphatase activity. Arbuscular mycorrhizal inoculation increased seedling dry weight.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: teak, alkaline phosphatase activity, Gigaspora sp, Glomus sp